Fique as thermal insulation morphologic and thermal characterization of fique fibers. Issue 1 (1st January 2019) - García Sánchez, Gabriel Fernando; Guzmán Lopez, Rolando Enrique; Restrepo Osorio, Adriana María; Arroyo, Emil Hernandez
Abstract: Bio-insulations have gained great interest in recent years due to their potential to reduce energy consumption without negative environmental impacts. Fique is one of the most important crops in Colombia, it has shown a low thermal conductivity which makes it a potential replacement for the common insulation materials. However, there are few works that study its thermal properties. In order to enhance the understanding of fique as thermal insulation, in this paper a morphological analysis of raw fique fibers and Thermogravimetry (TGA) and Differential Scanning Calorimetry (DSC) tests of three fique samples are presented, namely, natural fique without treatment, fique washed with a commercial softener and fique after having been soaked for 24 hours in the same softener.